RELASI MAKNA DALAM RUBRIK “AH… TENANE” KORAN SOLOPOS DAN RELEVANSINYA DENGAN PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH MENENGAH ATAS - Arif Wahyu Nugroho; Nugraheni Eko Wardani; Purwadi Purwadi (Universitas Sebelas Maret, 2018)
This research aims to describe: (1) the relation of meaning used in the rubric “Ah Tenane” newspaper SOLOPOS Edition April 2017; and (2) the relevance of the rubric “Ah Tenane” newspaper SOLOPOS 2017 Edition in Indonesian Language learning in high school. This research used a qualitative description of the approach. This type of research is the analysis of the contents. Sampling techniques using a purposive sampling method. Data collection using the technique of the analysis of the documents and interviews with informants. The validity of the data using triangulation theory and triangulation of sources. Data analysis using interactive analysis. Results of the study include: (1) the relation of meaning used in the rubric